Precision Full-Wave Rectifiers with Current Active Elements and Current Biasing - Lukas Langhammer; Jan Jerabek (International Journal of Advances in Telecommunications, Electrotechnics, Signals and Systems, 2013)
This article discusses universal precision rectifiers using current active elements and current sources for the diode excitation. The paper introduces circuit solution of the universal precision full-wave rectifier with intention to reduce negative effect of diode reverse recovery time. Furthermore, experimental results are given and a comparison of new circuit of precision full-wave rectifier and its known variant is presented.